(untitled) (Економіка і регіон/ Economics and region, 2019)
Budgetary security of a state is stipulated by a number of determinants that specify the content, structure and level of its provision. It is defined that the determinants of the state budget security are the factors, threats of both exogenous and endogenous origin as well as cause and effect relationships, which directly or indirectly determine its level and complexity of the processes of its ensuring. The list of the main determinants influencing the ensuring the budget security of the state taking into account the processes of globalization, constructive / destructive influence of factors and threats is offered. It is noted that the systematic element of the state budget security is the state budget, which is a multifaceted concept. The budget as an instrument of public policy plays a key role in ensuring the socio-economic development of the state, realization of its national interests, namely the volume and structure of the revenue and expenditure parts of the budget affect the functioning of all sectors of the economy. The necessity of ensuring budgetary security as a component of socio-economic development and the prerequisite for the implementation of effective state financial and economic policy as a basis for achieving the national economic interests of the state is substantiated. The main determinants of the impact on the budgetary security of the state have been systematized, taking into account the globalization processes and multicriteria of the existing factors and threats of both exogenous and endogenous origin.